ECOTOXICITY OF SODIUM ARSENITE ON EISENIA FETIDA - PALLAVI KAUSHIK; SONAM MEENA; MEGHA MATHUR (International Journal of Pharma and Bio Sciences, 2013)
In this study, we performed ecotoxicity tests of sodium arsenite on soil invertebrate Eisenia fetida. Initially, broad range of sodium arsenite (0.1, 1, 10, 100mg/ml) was tested for mortality of E. fetida after 24 hours in filter paper test. The narrow range doses (0-1mg/ml) were further tested to determine the EC50 and LD50. The EC50 dose of sodium arsenite was considered at which 50% of earthworms exhibited rejection to the spot on filter paper in the spot rejection test. The LD50 of sodium arsenite resulting in mortality in 50% of Eisenia fetida was studied with contact filter paper bioassay (24hrs) and soil bioassay (14 days). In the range finding test, there was no mortality in control and 0.1mg/ml but 100% mortality was observed at doses of 1mg and above after 24 hours. Thus, for further study smaller doses intervals in the range between 0-1mg/ml was selected for spot rejection, contact filter paper and soil bioassay. The percent mortality in each test was computed and was subjected to regression analysis to get a linear dose response curve and estimation of EC50 and LD50. The EC50 was estimated as 0.3mg/ml of sodium arsenite concentration to Eisenia fetida. The 24hrs- LD50 was estimated as 0.4mg/cm2 in filter paper and 14 days -LD50 as 5mg/kg in soil bioassay. Thus it can be concluded that Eisenia fetida exhibit sign of toxicity in environmental soils which are containing 1mg/kg and higher doses of sodium arsenite.